Eficácia da haptoglobina como marcador de hemólise no diagnóstico da síndrome HELLP - Higa, Thais Tiemi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Introduction: The HELLP syndrome is a severe complication of pregnant women with preeclampsia (PE), characterized by association of hemolysis, changes in liver enzymes and thrombocytopenia. Hemolysis, defined by the presence of microangiopathic hemolytic anemia, is one of the characteristics in this syndrome. However, as hemolysis occurs in a short time there is some difficulty in its laboratory diagnosis. Therefore, the search for a more sensitive and specific method for hemolysis determination may help in the early diagnosis of the HELLP syndrome. Objectives: a) To determine the plasma concentration of haptoglobin in normotensive pregnant women and in pregnant women with PE, classified into mild PE, severe PE and HELLP/partial HELLP syndrome; b) To compare the efficacy of haptoglobin plasma concentration and serum total bilirubin as criteria for hemolysis diagnosis in HELLP/partial HELLP syndrome. Methods: We conducted a cross-sectional analytical and comparative study involving 66 pregnant women diagnosed with PE, being 25 cases with mild PE, 28 with severe PE, and 13 with HELLP/partial HELLP syndrome. Twenty-one normotensive pregnant women were included for comparison of haptoglobin plasma concentration between the groups and to determine the normal values for pregnant women. The variables studied were: maternal age, gestational age, systolic and diastolic blood pressure, proteinuria, hematocrit and hemoglobin values, platelet count, serum total bilirubin, lactate dehydrogenase (LDH), glutamic oxaloacetic transaminase (AST) and glutamic-pyruvic transaminase (ALT), urea, creatinine and uric acid, and also plasma concentrations of haptoglobin. The results were analyzed by nonparametric tests, with a significance level of 5%. Results: The values of urea, uric acid, AST, ALT and LDH were significantly higher, while the number of platelets was lower in pregnant women with HELLP/partial HELLP syndrome compared to pregnant women with mild PE and ...

Introdução: A síndrome HELLP é uma complicação grave em gestantes portadoras de pré-eclâmpsia (PE), caracterizada por associação de hemólise, alteração de enzimas hepáticas e trombocitopenia. A hemólise, definida pela presença de anemia hemolítica microangiopática, é uma das características da síndrome. Entretanto, ainda existe dificuldade para a detecção da hemólise, uma vez que esta ocorre em curto espaço de tempo, sendo difícil constatá-la no diagnóstico laboratorial. Portanto, a busca por um método mais sensível e específico pode auxiliar no diagnóstico precoce da síndrome. Objetivos: a) Determinar a concentração plasmática de haptoglobina em gestantes normotensas e portadoras de PE, classificadas em PE leve, PE grave e com diagnóstico de síndrome HELLP/HELLP parcial; b) Comparar a eficácia entre a concentração plasmática de haptoglobina e de bilirrubina total, como parâmetros do diagnóstico de hemólise na síndrome HELLP/HELLP parcial. Métodos: Foi realizado estudo transversal, analítico e comparativo envolvendo 66 gestantes com diagnóstico de PE, sendo 25 casos de PE leve, 28 de PE grave e 13 com síndrome HELLP parcial ou síndrome HELLP. Foram incluídas 21 gestantes normotensas, para comparação da concentração plasmática da haptoglobina entre os grupos e determinar valores normais para gestantes. As variáveis estudadas foram: idade materna, idade gestacional, pressão arterial sistólica e diastólica, proteinúria, concentração de hematócrito e hemoglobina, contagem de plaquetas, concentração sérica de bilirrubina total, desidrogenase lática (DHL), transaminase glutâmico-oxalacética (TGO) e transaminase glutâmico-pirúvica (TGP), ureia, creatinina e ácido úrico, além da concentração plasmática de haptoglobina. Os resultados foram analisados por testes não paramétricos, com nível de significância de 5%. Resultados: Os valores de ureia, ácido úrico, TGO, TGP e ...
Keywords: Pre-eclampsia; Hemolise e hemolisinas; Síndrome HELLP; Mulheres grávidas; Gravidez - Complicações; Pregnancy - Complications